Factors Associated with Mortality at Harapan Kita Hospital (RSAB Harapan Kita) Secondary Data for 2024 - Nurhasanah; Indriyati, Titi; Prahastuti, Brian Sri (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Neonatal mortality remains a key public health indicator in Indonesia and represents a serious challenge in achieving the Sustainable Development Goals (SDGs). Although Jakarta has the lowest infant mortality rate compared to other provinces, the number of neonatal deaths at national referral hospitals like Harapan Kita Hospital remains quite high. Based on 2024 data, 220 deaths were recorded out of 1,634 births, with the main causes including low birth weight (LBW), asphyxia, prematurity, and infection. This situation highlights the importance of examining risk factors for both mothers and infants in neonatal mortality, particularly at Harapan Kita Hospital, Jakarta.  The research method used a quantitative approach with a retrospective case-control study design. Secondary data were obtained from maternal and infant medical records from January to December 2024. The study sample consisted of 94 respondents, consisting of 47 cases (neonatal deaths) and 47 controls (infants living >28 days or dying after >28 days), selected using a purposive sampling technique. Data analysis used univariate analysis and bivariate analysis with chi-square tests. The study showed that maternal factors associated with neonatal mortality were maternal nutritional status (p=0.021), type of delivery (p=0.014), and parity (p=0.037). Infant factors associated with neonatal mortality included low birth weight (p=0.000), prematurity (p=0.012), birth asphyxia (p=0.000), neonatal infection (p=0.001), and congenital abnormalities (p=0.018). Harapan Kita Jakarta Hospital needs to strengthen the referral system and coordination between hospitals, optimize the quality of antenatal care services, and improve human resource competency through training and workshops specifically for handling high-risk infants.